(untitled) (GAIMS Journal of Medical Sciences, 2026)
Bone health depends not only on bone mineral density (BMD) but also on microarchitectural integrity, which strongly influences skeletal strength and fracture risk. Conventional dual-energy X-ray absorptiometry (DXA), while widely used, provides only areal BMD and lacks the ability to capture three dimensional microarchitecture. This limitation is particularly important in premenopausal women, where fragility fractures may occur despite normal BMD values. High-resolution peripheral quantitative computed tomography (HR-pQCT) overcomes these shortcomings by enabling in vivo, three-dimensional assessment of trabecular and cortical compartments with high spatial resolution. The technique provides volumetric BMD, detailed microstructural parameters, and finite element analysis (FEA)-based estimates of mechanical competence. This review synthesizes current evidence on the application of HR-pQCT in premenopausal women. Normative data demonstrate generally favourable trabecular and cortical profiles in this group, yet studies reveal that women with idiopathic osteoporosis or fragility fractures exhibit significant cortical thinning, increased porosity, and disrupted trabecular organization despite near-normal BMD. HR-pQCT has also provided insights into skeletal alterations in metabolic disorders, diabetes, amenorrhea, and endocrine diseases, underscoring its role in detecting early microstructural compromise. Moreover, FEA derived from HR-pQCT images offers functional estimates of stiffness and failure load, strengthening its predictive value for fracture risk. Despite its clinical promise, HR-pQCT adoption is limited by cost, availability, and lack of standardized reference ranges for premenopausal women. Nonetheless, ongoing technological advances and longitudinal research are likely to establish HR-pQCT as an essential tool for early detection of skeletal fragility, monitoring treatment response, and guiding preventive strategies in young women.